Peptide cargo tunes a network of correlated motions in human leucocyte antigens. (26th March 2020) - Hopkins, Jade R.; Crean, Rory M.; Catici, Dragana A. M.; Sewell, Andrew K.; Arcus, Vickery L.; Van der Kamp, Marc W.; Cole, David K.; Pudney, Christopher R.
Abstract : Most biomolecular interactions are typically thought to increase the (local) rigidity of a complex, for example, in drug‐target binding. However, detailed analysis of specific biomolecular complexes can reveal a more subtle interplay between binding and rigidity. Here, we focussed on the human leucocyte antigen (HLA), which plays a crucial role in the adaptive immune system by presenting peptides for recognition by the αβ T‐cell receptor (TCR). The role that the peptide plays in tuning HLA flexibility during TCR recognition is potentially crucial in determining the functional outcome of an immune response, with obvious relevance to the growing list of immunotherapies that target the T‐cell compartment. We have applied high‐pressure/temperature perturbation experiments, combined with molecular dynamics simulations, to explore the drivers that affect molecular flexibility for a series of different peptide–HLA complexes. We find that different peptide sequences affect peptide–HLA flexibility in different ways, with the peptide cargo tuning a network of correlated motions throughout the pHLA complex, including in areas remote from the peptide‐binding interface, in a manner that could influence T‐cell antigen discrimination. Abstract : TCRs recognise peptide–HLA complexes mediating immune reactivity against pathogens and neoplasms. We investigated the drivers that govern molecular flexibility of different peptide–HLAs. We found that HLA motions were mediated by small alterations in the bound peptide, suggesting that allosteric mechanisms mediate HLA flexibility ('the tail wags the dog'). Our study sheds new light on the molecular mechanisms guiding protein dynamics in peptide–HLA, the major target for the TCR.